Application of fungal laccase in food processing and wastewater treatment - LIU Sixian, XIAO Shenghua, SUN Kai (Zhongguo niangzao, 2025)
Fungal laccase is a simple, efficient, energy-saving, and environmentally friendly green biocatalyst, which has extremely important application potential and commercial value in the field of food processing and wastewater treatment. Using O2 as a substrate, these enzymes induce single electron transfer of phenolic and non-phenolic compounds to produce water as the only by-product. At present, lignin in food and agricultural waste can be effectively oxidized and cleaved with laccase obtained by macrofungi fermentation culture, reducing energy consumption and cost. In addition, the laccase produced during the fermentation process can be recovered and recycled for application in food processing and wastewater treatment. The methods of producing fungal laccase from food industry by-products and agricultural waste were summarized, the latest research progress on the application of fungal laccase in improving the quality of fruit juice, wine, beer, bread and pectin gelation in food processing, as well as the treatment of food wastewater from wineries and olive oil plants were primarily highlighted, in order to provide theoretical basis and scientific guidance for expanding the application of fungal laccase in the field of food industry and environmental remediation.